Young, Innocent and Sexist? Social Differences in Benevolent and Hostile Sexist Attitudes towards Women amongst Flemish Adolescents. (February 2018) - Vandenbossche, Lauren; Spruyt, Bram; Keppens, Gil
Over the past few decades the position of women in Western societies has substantially improved in several domains. However, persistent inequalities remain and gender prejudice is thought to play a key role in this. In this article, we contribute to the literature which holds that in current Western societies, gender prejudice manifests itself in a more 'benevolent' form which encompasses subjectively favourable but patronizing attitudes towards women. We investigated the distribution of hostile sexism (HS) and benevolent sexism (BS) towards women amongst a large sample of Flemish adolescents ( N = 952). We found that while HS towards women is most prevalent amongst boys in technical and vocational education, girls in technical and vocational education also comply with macho culture. Moreover, these less educated girls also display the most BS towards women.